Follow-Up of Intracranial Aneurysms Treated with Matrix Detachable Coils: A Single-Center Experience - Mitra, D. (AJNR Am J Neuroradiol, 2007)
BACKGROUND AND PURPOSE: Matrix coils are polymer-coated bioactive coils used in treatment of intracranial aneurysms. The current study is aimed at evaluating the efficacy and safety of these coils in treatment of ruptured and unruptured aneurysms. METHODS: Seventy-seven consecutive patients with 84 aneurysms were included in the study. Forty-six aneurysms were treated with Matrix coils alone, and 38 were treated with Matrix coils in combination with other coils/devices. Angiographic follow-up was available in 64 patients with 70 aneurysms. Length of follow-up ranged from 6 to 28 months with mean of 10 months. Both postembolization and follow-up angiograms were graded on a 3-point Raymond scale. Aneurysms were classified as stable, improved, or recanalized based on the follow-up angiograms. Recanalization was considered major if it was saccular and its size would theoretically permit retreatment with coils. RESULTS: At the end of the initial procedure, 47 (56.0%) aneurysms showed complete occlusion (Raymond 1), 20 (23.8%) showed contrast filling the neck of the aneurysm (Raymond 2), and 16 (19.0%) showed contrast filling the sac of the aneurysm (Raymond 3). Of the 70 aneurysms in which follow-up angiograms were available, 55.7% remained stable in appearance, 20.0% showed improved occlusion, and 24.3% demonstrated recanalization; 8.6% demonstrated major recanalization. There were 2 aneurysm rebleeds (both incompletely packed); one resulted in death. CONCLUSION: Matrix coils are safe to use and the recanalization rate of aneurysms treated with these coils appears to be at least comparable with historical studies with Guglielmi detachable coils.